Taxonomic revision of Hemidactylus brookii Gray: a re-examination of the type series and some Asian synonyms, and a discussion of the obscure species Hemidactylus subtriedrus Jerdon (Reptilia: Gekkonidae) - Mahony, Stephen (Zootaxa, 2011)
The Hemidactylus brookii group taxon has received increased attention in recent years from systematists and taxonomists attempting to unravel the complicated issues of its synonyms. In this study, a morphological approach is adopted to reexamine the syntypes of Hemidactylus brookii and Hemidactylus subtriedroides. The syntype series of H. brookii is found to be composed of two morphologically distinct species. A Borneo syntype is designated as lectotype and redescribed in detail to provide taxonomic and nomenclatural stability for the species. A syntype of H. subtriedroides is designated lectotype and also redescribed in detail, along with additional populations, which includes the Australian paralectotype of H. brookii sensu lato. Hemidactylus subtriedroides is morphologically distinct from H. brookii sensu stricto, but indistinguishable from the recently elevated synonym Hemidactylus tenkatei with which it is here considered a junior subjective synonym. Neotypes are designated for the two Pakistan synonyms, Hemidactylus kushmorensis and Hemidactylus glead-